Carotid Atheroinflammation Is Associated With Cerebral Small Vessel Disease Severity - Evans, Nicholas R.; Tarkin, Jason M.; Walsh, Jessica; Chowdhury, Mohammed M.; Patterson, Andrew J.; Graves, Martin J.; Rudd, James H. F.; Warburton, Elizabeth A. (Frontiers in Neurology, 2021)
Background: Atherosclerosis is a systemic inflammatory disease, with common inflammatory processes implicated in both atheroma vulnerability and blood-brain barrier disruption. This prospective multimodal imaging study aimed to measure directly the association between systemic atheroma inflammation (“atheroinflammation”) and downstream chronic cerebral small vessel disease severity. Methods: Twenty-six individuals with ischemic stroke with ipsilateral carotid artery stenosis of >50% underwent 18fluoride-fluorodeoxyglucose-positron emission tomography within two weeks of stroke. Small vessel disease severity and white matter hyperintensity volume were assessed using 3-tesla magnetic resonance imaging also within two weeks of stroke. Results: Fluorodeoxyglucose uptake was independently associated with more severe small vessel disease (odds ratio 6.18, 95% confidence interval 2.1-18.2, P<0.01 for the non-culprit carotid artery) and larger white matter hyperintensity volumes (coefficient=14,328.1, P<0.01 for the non-culprit carotid artery). Conclusion: These proof-of-concept results have important implications for our understanding of the neurovascular interface and potential therapeutic exploitation in the management of systemic atherosclerosis, particularly non-stenotic disease previously considered asymptomatic, in order to reduce the burden of chronic cerebrovascular disease.